IMPROVEMENT OF CONSTRUCTIVE-TECHNOLOGICAL APPROACHES REDUCING INNOVATIVE OBSOLESCENCE OF INDUSTRIAL TECHNOLOGIES IN THE CONTEXT OF INDUSTRY 4.0 (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
The article is dedicated to the improvement of constructive-technological approaches in the design and manufacture of engineering products, innovations, their management and implementation in enterprises, innovation strategy and policies for its achievement, as well as methods for alternative solutions against the rapid obsolescence of innovations in the field of technology in the conditions of the Fourth Industrial Revolution (FIR) and globalization. Emphasis is on the stages in the design of the technological process for mechanical processing of engineering products, as well as the optimization of dimensional-accuracy connections. Schemes describing the optimization have been developed, and the approach will be programmatically implemented in subsequent development.